Technology Integration, Digital Proficiency, and Psychological Well-Being on Work Engagement: The Role of Self-Efficacy - Dian Kurniawan; Alfin Nur Fahmi Mufreni; Ane Kurniawati; Ali Subrata; Tine Badriatin (Program Studi Administrasi Negara Universitas Serang Raya, 2026)
Abstract The acceleration of digital transformation in Indonesia’s banking sector after 2025, driven by Bank Indonesia (BI) and the Financial Services Authority (OJK), focuses on innovation, financial inclusion, and the adoption of advanced technologies. This transformation requires employees readiness, particularly in technology integration, digital proficiency, and psychological well-being. Within this context, self-efficacy plays a critical role as a psychological mechanism that enables employees to adapt and enhance work engagement in the digital era. This study used a quantitative survey approach to analyze the influence of technology integration, digital proficiency, and psychological well-being on work engagement, with self-efficacy in the role of a mediating variable within banking employees in the Priangan Timur region. Data were collected through structured questionnaires and analyzed using structural equation modelling (SEM). The findings shows that technology integration, digital proficiency, and psychological well-being significantly affect self-efficacy, while self-efficacy itself affects a positive effect on work engagement. Furthermore, self-efficacy mediates the relationship between technology integration, digital proficiency, and psychological well-being on work engagement. These results suggest that employees with higher levels of self-efficacy are more capable of adapting to technological change, maintaining psychological health, and actively engaging in their work. This study contributes to the human resource management by highlighting the mediating role of self-efficacy in digital transformation contexts. Practically, it provides recommendations for banks to design strategies that combine technological adoption, digital skills development, and psychological support to sustain employee engagement. Future research may extend this study to other industries affected by digital transformation or addopt additional psychological factors to enrich the model. Keyword: Technology Integration; Digital Proficiency; Psychological Well-bein;, Work Engagement; Self-Efficacy.